Integration Processes in Latin America: The Case of Mexico and Central America - Flores Paredes, Joaquín; Wong Chan, Susana; Salas Chaverri, Duayner (Latin American Journal of Trade Policy, 2018)
After describing, within the framework of “Open Regionalism”, the tortuous process that the Central American countries have experienced to achieve their integration as a Common Market, this article analyses the relationship between these countries and Mexico, through the Free Trade Agreement signed among them. Once it is shown that the integration process of the Central American countries is on an impasse, the article explores the possibilities to advance on the economic integration between Mexico and the region. Using quantitative measurement and qualitative elements, this article identifies favorable conditions for such integration to be initiated by Mexico and Costa Rica, whether or not US trade policy changes towards the region.